Comparative clinical study of locking screws versus smooth locking pegs in volar plating of distal radius fractures. (September 2014) - Boretto, J. G.; Pacher, N.; Giunta, D.; Gallucci, G. L.; Alfie, V.; De Carli, P.
The present study was performed to test the null hypothesis on no difference in stability of fixation after volar plating of intra-articular distal radius fractures (AO C2-C3) with either locking smooth pegs or locking screws in a clinical setting. A retrospective evaluation included adult patients with C2-C3 AO fractures treated with a volar plate with locking smooth pegs or locking screws. Radiographic assessment was performed to evaluate extra- and intra-articular parameters in the early postoperative period and after bone union. Twenty-seven consecutive patients were included. Thirteen cases had fixation with locking screws and 14 had fixation with locking smooth pegs. Both groups had bone fragment displacement after fixation. However, there were no significant differences between the groups either in extra- or intra-articular parameters defined by Kreder et al. (1996). Our study shows that, in a clinical setting, there is no difference in stability fixation between locking screws or smooth locking pegs in C2-C3 distal radius fractures.